Iron Complexes of 4,5-Bis(diorganophosphinomethyl)acridine Ligands - Roca Jungfer, Maximilian; Rominger, Frank; Oeser, Thomas; Buchsteiner, Emilia; Hashmi, A. Stephen K.; Schaub, Thomas (Inorganic chemistry, 2024)
The search for an iron analog of the established ruthenium-based catalysts containing methylene-extended 4,5-bis(diorganophosphinomethyl)acridine ligands, [FeHCl(CO)(LR)], resulted in the discovery of a bidentate coordination mode of these usually tridentate pincer ligands toward iron. The acridines nitrogen atom does not coordinate to iron, leading to the formation of iron diphos-type complexes with unusually large cis bite angles of up to 124° as well as trans bite angles around 155°. The iron-containing complexes [FeCl2(κ2-LR)] (R = iPr, Ph), [FeX2(κ2-LCy)] (X = Cl, Br) and [Fe(CO)3(κ2-LR)] (R = iPr, Cy) have been isolated in crystalline form and characterized by spectroscopic methods and mass spectrometry. Their structures were verified unambiguously through X-ray diffraction. The stability of the iron(II) complexes decreased in the order Cy > Ph > iPr and Cl > Br > I, although all iron(II) complexes were found to be relatively stable enough for short-term handling in air in the solid state. Notably, no iron(0) complex of the phenyl derivative could be isolated. The iron(0) complex [Fe(CO)3(κ2-LCy)] was found to be significantly more stable toward hydrolysis and oxygen compared to [Fe(CO)3(κ2-LiPr)] and can be stored in air for months without significant decomposition in the solid state, while [Fe(CO)3(κ2-LiPr)] decomposes in air within seconds. The decomposition products [FeI2(κ2-O2LCy)], [{Fe(CO)3(κ2-HLR)}2] (R = iPr, Cy) and [FeCl2(CO)2(κ1-LCy)(κ1-OLCy)] were identified and characterized crystallographically. The iron(0) complex [Fe(CO)3(κ2-LCy)] is oxidized by [Fe(Cp)2](BPh4) to give the paramagnetic, low-spin iron(I) cation [Fe(CO)3(κ2-LCy)]+. The electron paramagnetic resonance spectrum of the highly sensitive cation as well as density functional theory calculations suggest a partial delocalization of the unpaired electron over the three carbonyl ligands and the acridines aromatic ring system. The catalytic activity and photophysical properties of the complexes have been preliminarily investigated.
Online veröffentlicht: 26. September 2024
Gesehen am 14.03.2025